The Perception of Mobile Assisted Language Learning by University Students in Batam - Jack Franco; Wilson Tungli; Asep Suryana; Reinaldi Arsani Runtu; Jo Sua (English Department, University of Riau Kepulauan, Batam,Indonesia, 2022)
We as humans often use language as a bridge to connect and communicate with each other. Globalization has played a role in bridging the gap through languages acknowledged around the globe, one of these that took center stage in becoming a truly global language is the English language. One of the biggest benefactors of a global language is the mobile device. however, mobile devices would be able to play the role of cementing the English language in its importance. Therefore, this research aimed to learn how effectively can the perception of mobile devices be helped in learning the English Language, with the research focusing on higher educational environments such as university students in Batam City. This research was quantitative research using the Technology Acceptance Model and had dependent variables covering attitude towards using, and the behavioral intention of using. A total of 384 Respondent’s data was collected for this research. In the end, the conclusion was that Mobile Assisted Language Learning (MALL) is proven to be effective in affecting those that used it. However, this would not discredit those that didn’t have the intention to learn through a mobile device in the first place or those without a mobile device.